WEED CONTROL EFFICIENCY OF HERBICIDE SULFOSULFURON IN POTATO CROP - singh, shiv pratap; NA, Sanjay Rawal; Dua, Vijay Kumar; Sharma, Sanjay Kumar (Potato Journal, 2018)
Potato J (2017) 44 (2): 110-116SP Singh1 , S Rawal2 , VK Dua3 and SK Sharma1ABSTRACT: A field study was carried out at ICAR-CPRS, Gwalior during two cropping seasons (2013-14 and 2014– 15) to evaluate the effectiveness of sulfosulfuron as post-emergence herbicide in potato crop in west central region of India. The weed flora mainly included Chenopodium murale (Kharbathua), Chenopodium album (Bathua), Celosia argentea (white cock’s comb) and Echinochloa crusgallis (Sanwa). Application of sulfosulfuron herbicide was very effective in reducing weed count. Sulfosulfuron (25 g a.i./ha) had comparable weed dry weight (11 g/m2 ) to weed free treatment (7 g/m-2). Weed control index was also comparable in sulfosulfuron treatment applied at 25 g a.i./ha (93) with weed free plot (96). Shoot number per plant were not affected by sulfosulfuron levels, however irrecoverable photo-toxicity symptoms were observed after application of sulfosulfuron on potato which caused stunted growth of potato plants and reduced tuber yield. At 60 days revealed that plant height (39.5 cm) was significantly lower with sulfosulfuron (25 g a.i./ha) as compared to weed free plot (46 cm) and total tuber yield was also significantly less (23.9 t/ha) than weed free plot (29.4 t/ha). Weed control efficiency (62) and herbicide efficiency index (3) were lower, but statistically comparable to weed free check. Although sulfosulfuron (25 g a.i./ha) was highly effective in controlling different weeds in the present study, its application had no effect on tuber yield (23.9 t/ha), which was at par with that under weedy check (20.7 t/ha) due to phyto-toxic effect. Significant reduction in yield does not favour its use as post-emergence herbicide in potato crop.